Inhibitory effect of modified silkworm pupae oil in PDGF-BB-induced proliferation and migration of vascular smooth muscle cells - Kim, Young Jin (Food Sci Biotechnol, 2020)
Silkworm pupae oil (SPO) has been reported to have various biological activities in improving blood circulation. However, the protective action of SPO against vascular disorders remains unknown. A new formulation of SPO was prepared through an esterification and saponification process. The composition of unsaturated fatty acids in silkworm pupae oil sodium salt (SPOS) was then analyzed by LC/MS to show α-linolenic acid (11.0%), linoleic acid (73.2%), palmitic acid (3.1%), oleic acid (12.0%), and stearic acid (0.7%). The in vitro studies were performed to find out the efficacy of SPOS on platelet-derived growth factor (PDGF-BB) induced vascular smooth muscle cell (VSMC) migration and proliferation. PDGF-BB (10 ng/mL) induced abnormal migration and proliferation of VSMCs, whereas exposure to SPOS (30 μg/mL) significantly reduced the PDGF-BB-induced cell migration and proliferation. The extracellular signal-regulated kinase1/2 (ERK1/2) and phosphorylation of ERK1/2 were determined by immunoblot analysis and the ERK1/2 phosphorylation in PDGF-BB-stimulated VSMCs was downregulated by SPOS (30 μg/mL) treatment. These results indicate that SPOS may be a helpful and useful agent as a functional food and drug against vascular disorders.